Coincident Multimessenger Bursts from Eccentric Supermassive Binary Black Holes - Vikram Manikantan; Vasileios Paschalidis; Gabriele Bozzola (The Astrophysical Journal Letters)
Supermassive binary black holes are a key target for the future Laser Interferometer Space Antenna and excellent multimessenger sources across the electromagnetic (EM) spectrum. However, unique features of their EM emission that are needed to distinguish them from single supermassive black holes are still being established. Here, we conduct the first magnetohydrodynamic simulation of disk accretion onto equal-mass, nonspinning, eccentric binary black holes in full general relativity, incorporating synchrotron radiation transport through the dual jet in postprocessing. Focusing on a binary in the strong-field dynamical spacetime regime with eccentricity e = 0.3 as a point of principle, we show that the total accretion rate exhibits periodicity on the binary orbital period. We also show, for the first time, that this periodicity is reflected in the jet Poynting luminosity and the optically thin synchrotron emission from the jet base. Furthermore, we find a distinct EM signature for eccentric binaries: they spend more time in a low emission state (at apocenter) and less in a high state (at pericenter). Additionally, we find that the eccentric binary quasiperiodic gravitational-wave (GW) bursts are coincident with the bursts in Poynting luminosity and synchrotron emission. Finally, we discuss how multimessenger EM and GW observations of these systems can help probe plasma physics in their jet.